Cooperative learning as a strategy of improving mathematics performance and attitudes - Ndebil, Matthew Bugre; Ali, Clement Ayarebilla (International Journal of Educational Innovation and Research, 2024)
There has been an increasing concerns that the traditional instructional methods militate against students’ performance and positive attitudes towards school mathematics. This study employs cooperative learning strategy to provide an innovation as a way of ameliorating the canker. We utilised the quasi-expermental (prepost non-equivalent) design. In this design, two senior high schools selected. One school was the experimental (SHS A) and the other was the control (SHS B). A sample of 224 students were assigned to the experimental (110) and control (114) groups. After treatments, mathematics achievement tests were used to gather the data. The data was analysed with means, standard deviations, percentages, p-values and t-statistics. The outcomes revealed that students who had tutorials in the cooperative strategy performed better than those who had tuition through the traditional. Even within the experimental group, there was no statistically significance differences between boys and girls. It was concluded that students’ performance and attitudes toward learning mathematics were positively enhanced by cooperative learning. It was therefore recommended that stakeholders make conscious efforts to inspire teachers to model more cooperative learning techniques in mathematics instruction.